Blockchain and publishing: towards a publisher-centred distributed ledger for the book publishing industry. Issue 1 (2nd January 2023) - Ryan, Mark David; Macrossan, Phoebe; Wright, Sue; Adams, Michael
Abstract: There is a small but growing volume of scholarly research and technological experiments in relation to blockchain and book publishing. However, to date, appropriate and feasible blockchain models for rights management and copyright exploitation remain largely untested. Furthermore, extant research has focussed on author-centred models of intellectual property and royalty management, with limited focus on publisher-centred models. Consequently, there are few practical prototypes and little understanding of blockchain models that are mutually beneficial for both writers and publishers. This article presents the findings of a two-year research project, No Point in Stopping, that explores a publisher-centred model of blockchain publishing that creates value for micro-publishers. The project developed a custom blockchain prototype and digital ledger to manage intellectual property agreements, royalty payments, and the tracking of both physical in-store and online purchases. The authors argue that for publishers, blockchain can create and monetise new digital publishing products from the drafting and editing process, thereby using intellectual property that would normally be an input into the publishing process rather than a commercial output. Blockchain can also create a new contract and revenue system that disrupts the current fee-for-service model by paying royalties to all creative professionals involved in this publishing process.